Clinical Evaluation of Coded Herbal Medicine (Hypoess) and Angiotensin Receptor Blocker (Candesartan) in Essential Hypertensive Patients (Medical Forum Monthly, 2024)
Objective: The basic aim of this research study was to determine the comparative effect of herbal treatment in comparison with standard allopathic medicine in control and treatment of essential hypertensive patients.Study Design: Prospective and comparative studyPlace and Duration of Study: This study was carried out in Department of Pharmacology, HCM&D, FH&MS, Hamdard University, Karachi, from January 2014 to July 2014.Materials and Methods: A total of 200 patients were enrolled in study and were given Hypoess in one hundred patients while remaining one hundred patients received allopathic medicine Candesartan.Results: In test group one hundred patients were treated with herbal drug (Hypoess) and it decreased mean systolic blood pressure of study patients with a decrease of 15.17% whereas, a reduction of 20.56% was found with allopathic medicine Candesartan Cilexetil. Similarly a decrease of 18.07% was found in mean diastolic blood pressure with herbal medicine in test group patients and a decrease of 21.65% was observed in case of allopathic drug in mean diastolic blood pressure of control group patients.Conclusion: The effects of herbal medicine were found statistically significant in controlling blood pressure and it has been found as an alternative option to treat essential hypertensive patients with its cost-effectiveness.